2006
DOI: 10.1002/anie.200601178
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Intramolecular Carbothiolation of Alkynes: Synthesis of 2,3‐Disubstituted Benzothiophenes from (αAlkoxy Alkyl) (ortho‐Alkynyl Phenyl) Sulfides

Abstract: Gold forms rings: AuCl‐catalyzed cyclization of (α‐alkoxy alkyl) (ortho‐alkynyl phenyl) sulfides 1 proceeds under mild conditions to give 3‐(α‐alkoxy alkyl) benzothiophenes 2 in high yields for a wide range of substrates (see scheme). The starting materials are readily available through acetalization of ortho‐bromobenzenethiol and subsequent Sonogashira coupling. This methodology provides an atom‐economic route to sulfur‐containing heteroarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(93 citation statements)
references
References 35 publications
0
93
0
Order By: Relevance
“…However, Yamamoto described the attack of the sulfur atom of aryl thioethers to afford benzothiophenes (equation 31). 152 More recently, it has been showed that propargylic thioethers or thioacetals undergo migration to give carbenes that cyclize in hydroarylation processes 153 and thiocarbamates that evolve by propargylic rearrangement. 154 Thiosilanes can perform as both sulfur nucleophiles and silicon electrophiles in intramolecular reactions to afford benzothiophenes (equation 32).…”
Section: Sulfur Nucleophilesmentioning
confidence: 99%
“…However, Yamamoto described the attack of the sulfur atom of aryl thioethers to afford benzothiophenes (equation 31). 152 More recently, it has been showed that propargylic thioethers or thioacetals undergo migration to give carbenes that cyclize in hydroarylation processes 153 and thiocarbamates that evolve by propargylic rearrangement. 154 Thiosilanes can perform as both sulfur nucleophiles and silicon electrophiles in intramolecular reactions to afford benzothiophenes (equation 32).…”
Section: Sulfur Nucleophilesmentioning
confidence: 99%
“…Gold-catalyzed cyclization of -alkoxyalkyl(ortho-alkynylphenyl)sulfides gave 2,3-disubstituted benzothiophenes in excellent yields. 89 Similarly, gold-catalyzed cyclization of (ortho-alkynylphenylthio)silanes gave 3-silyl-substituted benzothiophenes. Gold-catalyzed and/or copper-catalyzed benzannulation reactions between orthoalkynylbenzaldehydes 22 and alkynes gave naphthyl carbonyl compounds 23 in high to good yields (Scheme 7).…”
Section: Scheme 5 Indene Synthesis Via C-o Bond Additionmentioning
confidence: 99%
“…Indeed, the method represents a thiophene skeleton, which would provide a more efficient and practical route, are extremely rare in the literature presumably because of catalyst poisoning by sulfur. Only a few reports in which gold 57) or palladium 58) catalysts have been used to effect C-S bond formation have appeared.…”
Section: -46)mentioning
confidence: 99%